Synthesis, Antibacterial and Antifungal Activity of Some Iodo-Substituted 3,5-Diaryl Isoxazolines - Patil, S.D.; Gudadhe, S.K.; Ukesh, C.S.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some iodo-substituted ortho-hydroxy chalcones, flavanones and iodo-substituted 3,5-diarylisoxazolines were synthesized and tested for antibacterial activities against Staphylococcus aureus, Escherichia coli, Proteus mirabilis, Enterobacter aerogenes, Pseudomonas aeruginosa and antifungal activities against Curvularia and Colletotrichum. Title compounds were found effective against both bacteria (MIC 25–100 μg/mL) and fungal species (57–100% spore germination inhibition).